Taxonomic notes on South American Miconia (Melastomataceae). II - Goldenberg,Renato (2010)
Abstract We propose nine new synonyms, and five lectotypifications for South American Miconia (Melastomataceae). Miconia paulensis is synonymized under M. cinerascens var. cinerascens ; M.conferta as a synonym of M. inconspicua; Miconia riedelii and M. langsdorffii as a synonym of M. paucidens; M. camposnovaesii and M. coralliocarpa as a synonym of M. pseudonervosa ; and M. hispida, M. regnellii and M. brevipes var. longifolia under M. trianae. We propose lectotypes for M. conferta, M. hispida, M. langsdorffii, M. pseudonervosa, and M. trianae.